La rappresentazione dell'Africa nella musica leggera italiana: dalle prime esperienze coloniali al Fascismo - Bussotti, L. (Africa e Mediterraneo, 2015)
The Italian colonial experience in Africa, which started at the end of the 19th century, introduced a set of images of the continent that influenced many artistic fields in Italy. Such representations of Africa also remained strong during the second wave of colonial expansion under the fascist regime, with an added touch of racism towards the African culture. Despite a partial revision of the negative African stereotypes after the end of Fascism, Italian art, and in particular music, was only able to get rid of its "exotic" outlook on Africa at the beginning of the 1980s.